Calcineurin Governs Thermotolerance and Virulence of Cryptococcus gattii - Chen, Ying-Lien (Genetics Society of America, 2013)
The pathogenic yeast Cryptococcus gattii, which is causing an outbreak in the Pacific Northwest region of North America, causes life-threatening pulmonary infections and meningoencephalitis in healthy individuals, unlike Cryptococcus neoformans, which commonly infects immunocompromised patients. In addition to a greater predilection for C. gattii to infect healthy hosts, the C. gattii genome sequence project revealed extensive chromosomal rearrangements compared with C. neoformans, showing genomic differences between the two Cryptococcus species. We investigated the roles of C. gattii calcineurin in three molecular types: VGIIa (R265), VGIIb (R272), and VGI (WM276). We found that calcineurin exhibits a differential requirement for growth on solid medium at 37°, as calcineurin mutants generated from R265 were more thermotolerant than mutants from R272 and WM276. We demonstrated that tolerance to calcineurin inhibitors (FK506, CsA) at 37° is linked with the VGIIa molecular type. The calcineurin mutants from the R272 background showed the most extensive growth and morphological defects (multivesicle and larger ring-like cells), as well as increased fluconazole susceptibility. Our cellular architecture examination showed that C. gattii and C. neoformans calcineurin mutants exhibit plasma membrane disruptions. Calcineurin in the C. gattii VGII molecular type plays a greater role in controlling cation homeostasis compared with that in C. gattii VGI and C. neoformans H99. Importantly, we demonstrate that C. gattii calcineurin is essential for virulence in a murine inhalation model, supporting C. gattii calcineurin as an attractive antifungal drug target.